2000
DOI: 10.1046/j.1365-2745.2000.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in allozyme frequencies inFestuca ovinapopulations after a 9‐year nutrient/water experiment

Abstract: Summary 1The grass Festuca ovina is an important constituent of the species-rich`alvar' grasslands on the Baltic island of O È land. Levels of allozyme polymorphism are high and variation is known to be correlated with habitat variation (soil moisture, pH and depth). 2 A 9-year ®eld experiment on species diversity provided replicate plots (in three sites) that had been subjected to six di erent experimental treatments (control; N P K; P K; N K; K; water). 3 Samples of F. ovina were collected and analyses of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 70 publications
(125 reference statements)
3
36
1
Order By: Relevance
“…In addition to phenological segregation, differential natural selection along a snowmelt gradient might be important for the development of spatial patterns of genetic variation. Some allozyme studies at microgeographic scales suggest that changes in gene frequencies reflecting environmental gradients are indeed caused by natural selection (eg Allard et al, 1993;Linhart and Grant, 1996;Prentice et al, 2000). In our study, only species having excess homozygotes within populations showed a significant genetic structure along the phenological gradient.…”
Section: Discussionsupporting
confidence: 55%
“…In addition to phenological segregation, differential natural selection along a snowmelt gradient might be important for the development of spatial patterns of genetic variation. Some allozyme studies at microgeographic scales suggest that changes in gene frequencies reflecting environmental gradients are indeed caused by natural selection (eg Allard et al, 1993;Linhart and Grant, 1996;Prentice et al, 2000). In our study, only species having excess homozygotes within populations showed a significant genetic structure along the phenological gradient.…”
Section: Discussionsupporting
confidence: 55%
“…Many grasses have been reported to evolve locally adapted populations as a response to spatially varying selection forces (Prentice et al 1995;Linhart and Grant 1996). For example, grazed populations of Poa pratensis have been found to be genetically shorter than ungrazed populations, indicating a selective advantage of short stature under grazing management (Kemp 1937).…”
Section: The Structuring Of Quantitative Genetic Variationmentioning
confidence: 99%
“…Indeed, the distributional and genetic pattern of many mountain species suggested biogeographical connections between the Bulgarian mountains and the Southern Carpathians (Reed et al 2004;Puşcaş et al 2008;Varga and Schmitt 2008;Schmitt 2009). It has been demonstrated that, despite the assumed selective neutrality of allozyme markers (e.g., Kimura 1968), environmental factors (temperature, humidity) can promote a shift in allele frequencies in populations through directional selection mechanisms (Koehn and Hilbish 1987;Karl and Avise 1992;Prentice et al 2000;Karl et al 2009). Thus, more similar environmental conditions between the southeastern Carpathians and the Balkans might be another reason of grouping of southeastern Carpathian P. ullepitschii and P. rhodopea populations.…”
Section: Correspondence Between Allozyme and Morphological Differentimentioning
confidence: 99%